Demonstration of fast‐acting protection as a key enabler for more‐electric aircraft interconnected architectures. Issue 2 (1st June 2017) - Kostakis, Theodoros; Norman, Patrick J.; Galloway, Stuart J.; Burt, Graeme M.
Abstract : Driven by anticipated fuel‐burn and efficiency benefits, the more‐electric aircraft (MEA) concept is a technological shift in the aviation industry, which seeks to replace mechanical, hydraulic and pneumatic functions with electrical equivalents. This shift has greatly increased the electrical power demands of aircraft and has made MEA networks larger and more complex. Consequently, new and more efficient electrical architectures are required, with interconnected generation potentially being one design approach that could bring improved performance and fuel savings. This study discusses the current state of interconnected generation in the aviation industry and key technological advances that could facilitate feasible interconnection options. This study demonstrates that interconnected systems can breach certification rules under fault conditions. Through modelling and simulation, it investigates the airworthiness‐requirements compliance of potential impedance solutions to this issue and quantifies the potential impact on system weight. It concludes by identifying fast fault clearing protection as being a key enabling technology that facilitates the use of light‐weight and standards‐compliant architectures.